CHARACTERISTICS OF JOHN DEWY'S PROJECT TECHNOLOGY IN PERSONAL FORMATION IN MODERN EDUCATION (American Journal of Interdisciplinary Research and Development, 2022)
In this article, at the beginning of the 20th century, the well-known pedagogue John Dewey and his follower U. X. Project technology created by Kilpatrick, its content - essence, main concepts, its types, stages of using Project technology and project annotation created for the purpose of using this technology are covered.